Hydrothermal liquefaction of spent coffee grounds in water medium for bio-oil production. (March 2016) - Yang, Linxi; Nazari, Laleh; Yuan, Zhongshun; Corscadden, Kenneth; Xu, Chunbao (Charles); He, Quan (Sophia)
Abstract: Spent coffee grounds (SCG) were liquefied in hot-compressed water to produce crude bio-oil via hydrothermal liquefaction (HTL) in a 100 cm 3 stainless-steel autoclave reactor in N2 atmosphere. We investigated the effects of operating parameters such as retention times (5 min, 10 min, 15 min, 20 min and 25 min), reaction temperatures (200 °C, 225 °C, 250 °C, 275 °C and 300 °C), and water/feedstock mass ratios (5:1, 10:1, 15:1 and 20:1) and initial pressure of process gas (2.0 MPa and 0.5 MPa) on the yield and properties of the resulting crude bio-oil. The highest yield of the crude bio-oil (47.3% mass fraction) was obtained at conditions of 275 °C, 10 min retention time and water/feedstock mass ratio of 20:1 with an initial pressure of 2.0 MPa. The elemental analysis of the produced crude bio-oil revealed that the oil product had a higher heating value (HHV) of 31.0 MJ kg −1, much higher than that of the raw material (20.2 MJ kg −1 ). GC–MS and FT-IR measurements showed that the main volatile compounds in the crude bio-oil were long chain aliphatic acids and esters. Highlights: First demonstration of spent coffee grounds as a feedstock for the hydrothermal liquefaction (HTL) process. Optimal HTL conditions: 275 °C reaction temperature, 10min reaction time, 20:1 mass ratio of water and SCG. The maximum crude bio-oil yield was 47.3% mass fraction with a higher heating value of 31 MJ·kg-1. Alternative option for biological residues treatment.